Evaluation of angiogenic and embryotoxic activity of the extract of Anadenanthera peregrina (Angico-do-Cerrado) - Marinho, Tamíris Augusto; Nunes, Patrícia Silva; Lino Junior, Ruy de Souza; Reis, Paulo Roberto de Melo; Machado, Mônica Rodrigues Ferreira; Silva Junior, Nelson Jorge; Menezes Filho, Antonio Carlos Pereira de; Ventura, Matheus Vinicius Abadia (Brazilian Journal of Science, 2022)
The genus Anadenanthera has been reported in the literature with antioxidant, anti-inflammatory, antimicrobial effect and healing action in wound treatment. The study aimed to evaluate, in vivo, the angiogenic and embryotoxic activities of A. peregrina extract. Angiogenesis in chicken embryo egg chorioallantoic membrane and zebrafish embryotoxicity was performed. A. peregrina extract at concentrations 62 mg mL-1 and 124 mg mL-1 were angiogenic. For embryotoxicity, the mortality rate increased with increasing concentration and increased dose and time dependent embryotoxicity was observed. The lethal concentration (LC50) ranged from 0.331mg mL-1 over the 24 hpf period to 0.007 mg mL-1 at 168 hpf (Δ% = -97.9), decreasing with increasing exposure. The heart rate decreased progressively and significantly with increasing concentration at all tested exposure times. In conclusion, it was evidenced that the extract of Anadenanthera peregrina has angiogenic activity. Nonetheless, embryotoxic effects were observed at high concentrations.